Sustainable waste management of health services in Brazil (Research, Society and Development, 2023)
Introduction: health service waste is generated in environments that provide care to human and animal health. Some of these wastes according to their properties may pose risks to public health and the environment. The environmental damage resulting from the disposal of hospital equipment is quite significant, and in order to minimize these problems, adequate procedures for the correct disposal have been created. Objective: to describe the sustainable management of waste from health services in Brazil. Methods: This is a narrative literature review study. Articles retrieved from the secondary databases Virtual Health Library (VHL), Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (Scielo) and Online System for Search and Analysis of Medical Literature (MEDLINE) were analyzed using the descriptors waste from health services, environmental impacts, sustainability and waste management plan. We considered studies published in Portuguese, English or Spanish and that dealt directly with the theme object of study. Results: regulatory bodies must offer legal and efficient support and waste generating services must recognize the importance of proper management with responsible management and committed to the implementation of sustainable measures. Conclusion: to be possible a sustainable management, it is essential to implement an efficient selective collection and recycle the material, since recycling pollutes less, because it reduces the volume of waste to be discarded.